Automatic measurement of shear wave splitting and applications to time varying anisotropy at Mount Ruapehu volcano, New Zealand - Savage, M. K.; Wessel, A.; Teanby, N. A.; Hurst, A. W. (Journal of Geophysical Research: Solid Earth, 2010)
We present an automatic shear wave splitting measurement tool for local earthquakes, with the sole manual step of choosing an S arrival time. We apply the technique to three data sets recorded on Mount Ruapehu volcano in New Zealand that have previously been determined to have fast polarizations that vary in time and with earthquake depth. The technique uses an eigenvalue minimization technique, applied over multiple measurement windows. The dominant period of each waveform sets minimum and maximum window lengths. Cluster analysis determines the best solution among all the windows, and quality grading criteria assess the results automatically. When the same filters are used for events determined to be high quality from manual studies, the automatic technique returns virtually identical results. Scatter increases when the automatic technique chooses the best filter, but the average automatic results remain consistent with the manual results. When the automatic technique is used on sets that include data previously judged as poor quality, some stations yield distributions of fast polarizations that include peaks that were not present in previously published results. The difference may stem from two factors: automatic grading lets through some measurements that independent analysts consider poor quality, but also unconscious bias in the manual selection process may downgrade measurements that do not fit expectations. Nonetheless, the new objective analysis confirms changes in the average fast polarizations between 1994 and 2002 and between shallow and deep events. Therefore, this new technique is valuable for objective assessment of anisotropy and its variation in time.